Staphylococcus aureus Uses a Novel Multidomain Receptor to Break Apart Human Hemoglobin and Steal Its Heme - Spirig, Thomas (American Society for Biochemistry and Molecular Biology, 2013)
Staphylococcus aureus is a leading cause of life-threatening infections in the United States. It requires iron to grow, which must be actively procured from its host to successfully mount an infection. Heme-iron within hemoglobin (Hb) is the most abundant source of iron in the human body and is captured by S. aureus using two closely related receptors, IsdH and IsdB. Here we demonstrate that each receptor captures heme using two conserved near iron transporter (NEAT) domains that function synergistically. NMR studies of the 39-kDa conserved unit from IsdH (IsdH(N2N3), Ala(326)–Asp(660)) reveals that it adopts an elongated dumbbell-shaped structure in which its NEAT domains are properly positioned by a helical linker domain, whose three-dimensional structure is determined here in detail. Electrospray ionization mass spectrometry and heme transfer measurements indicate that IsdH(N2N3) extracts heme from Hb via an ordered process in which the receptor promotes heme release by inducing steric strain that dissociates the Hb tetramer. Other clinically significant Gram-positive pathogens capture Hb using receptors that contain multiple NEAT domains, suggesting that they use a conserved mechanism.